Bundled Payment Plans Are Associated With Notable Cost Savings for Ambulatory Outpatient Total Shoulder Arthroplasty. Issue 19 (1st October 2020) - Walters, Jordan D.; Walsh, Ryan N.; Smith, Richard A.; Brolin, Tyler J.; Azar, Frederick M.; Throckmorton, Thomas W.
Abstract : Introduction: Bundling of services, typically into a 90-day episode of care, is intended to facilitate cost reduction. The purpose of this study was to determine the impact of a private insurance bundling program on the costs of outpatient total shoulder arthroplasty (TSA) at a freestanding ambulatory surgery center. Methods: A cost minimization analysis was done of patients who had anatomic TSA by a single surgeon at a single freestanding ambulatory surgery center, including line-by-line comparisons of demographic and comorbidity factors for all patients treated within the 90-day episode of care. Results: Seventy-six primary anatomic TSAs were included, 39 in the bundled group and 37 outside of the program. The bundled group was on average older (58 years) than the unbundled group (54 years, P = 0.021), but the groups were otherwise similar in demographics. The average total implant charges were significantly less for the bundled group (24, 822.43 versus 28, 405.51, P = 0.014). Average total surgery supply charges and anesthesia supply charges were similar ( P > 0.05). Mean total outpatient surgical day charges (implants, surgical, and anesthesia equipment) were significantly less for the bundled group (29, 782.43 versus 33, 238.68, P = 0.022), as were average operating room staffing costs (135.37 versus 162.55, P = 0.015). During the 90-day postoperative period, charges were similar. Conclusions: Primary anatomic TSA using a bundled care program in an outpatient setting coincides with markedly lower charges. The primary driver of this reduction is implant pricing, which is negotiated as part of the bundle. Surgeons must carefully analyze their unique practices in the changing economic health care environment when creating an outpatient TSA and/or bundling program. Level of evidence: Level III economic analysis